Breast self-examination and the role of education based on stages of change model in changing women's decision - Mohammad Matlabi; Abdaldjvad Khajavi; Fariba Askari; Maryam Saberi (Mashhad University of Medical Sciences, 2018)
Introduction: Breast cancer is considered as a serious health concern worldwide. The early diagnosis of this disease plays an important role in reducing its associated mortality rate. Regarding this, the present study was conducted with the aim of investigating the role of training in changing the breast self-examination behavior among the females living in Gonabad, Iran. Method: This field trial was conducted on 140 married women within the age range of 20-49 years in Gonabad in 2016. The study population was selected using simple random sampling technique, and then assigned into two groups of control and intervention. The intervention group was subjected to breast self-examination training. The breast self-examination behavior was investigated using the Stages of Change Model. The participants filled out a questionnaire, covering the demographic information and the stages of changes, before, immediately after, and three months after the educational intervention. The data were analyzed in SPSS (version 20) using statistical tests, such as repeated measures ANOVA, Student's t-test, Chi-square test, and multivariate ANOVA. P-value less than 0.05 was considered statistically significant. Findings: According to the results, the majority of the women in both intervention and control groups were in pre-contemplation and contemplation stages prior to the intervention. The results of the Chi-square test revealed no significant difference in change stages before the intervention (P=0.609). However, immediately and three months after the training, most of the subjects in the intervention group moved to action and maintenance stages, while in the control group, the majority of the women were in pre-contemplation and contemplation stages. Conclusion: As the findings indicated, educational intervention based on the stages of change model was effective in the improvement of breast self-examination behaviors. Moreover, training based on this model could lead to the promotion of screening behaviors depending on the stage of changes at which the women are.